Analysis of Chemical Teaching Materials for Class X SMA/MA on The Discussion of The Role of Chemistry in Daily Life - Sandy Yudha; Oddy Azis Saputra; Rudi Purwanto; Asep Wahyu Nugraha; Saranom Silaban (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Abstract: Analysis of chemical teaching materials for class X SMA/ MA on the discussion of the role of chemistry in daily life. The purpose of this study was to analyze the concept labels and the suitability of teaching materials to the K13 curriculum on the role of chemistry in everyday life and identify those that would cause misconceptions in chemistry books. The method used in this research is descriptive qualitative method. The instrument used to obtain the data is the Concept Analysis Table which is adapted to the KD in the K13 curriculum syllabus and reviews that will lead to conceptual errors. The results showed that the number of concept labels analyzed was 20 concept labels in total, the concept labels in book A and book B which corresponded to the 2013 curriculum syllabus were 14 and 18 respectively. The same concept labels between book A and book B amounted to 12, and the concept labels that are only found in book B are 5 and all are in accordance with the K13 curriculum syllabus. Reviews that give rise to conceptual errors in book A contained in the concept label The Nature of Chemistry. While in book B, there are no errors that have the potential to cause misconceptions. This also affects students who will cause misconceptions if the teaching materials used are incomplete in explaining the concepts even though the teacher can explain in detail.Keywords: analysis, textbook, the role of chemistry in lifeAbstrak: Analisis bahan ajar kimia kelas X SMA/MA pada pembahasan peran kimia dalam kehidupan sehari-hari. Tujuan Penelitian ini untuk menganalisa label konsep dan kesesuaian materi ajar terhadap kurikulum K13 pada materi peran kimia dalam kehidupan sehari-hari dan mengidentifikasi yang akan menimbukan kesalahan konsep pada buku kimia. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif. Instrumen yang digunakan untuk memperoleh data adalah Tabel Analisis Konsep yang disesuaikan dengan KD pada Silabus kurikulum k13 dan ulasan yang akan menimbulkan kesalahan konsep. Hasil penelitian menunjukkan Jumlah label konsep yang dianalisis berjumlah 20 label konsep secara keseluruhan, label konsep pada buku A dan buku B yang sesuai terhadap silabus kurikulum 2013 masing-masing berjumlah 14 dan 18. Label konsep yang sama antara buku A dan buku B berjumlah 12, dan label konsep yang hanya terdapat pada buku B berjumlah 5 dan semua sesuai terhadap silabus kurikulum K13. Ulasan yang menimbulkan kesalahan konsep pada buku A yang terdapat pada label konsep Hakikat Ilmu kimia. Sedangkan pada buku B tidak ditemukan adanya kesalahan yang berpotensi mengakibatkaan miskonsepsi. Hal ini juga berpengaruh pada siswa yang akan menimbukan  miskonsepsi jika bahan ajar yang digunakan kurang lengkap dalam menjelaskan konsep-konsepnya walaupun guru bisa saja menjelaskan secara detail.Kata Kunci: analisis, buku teks, peran kimia dalam kehidupanDOI:10.23960/jppk.v10.i3.2021.11